2005
DOI: 10.1111/j.1540-8167.2005.50028.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Atrial Antiarrhythmic Action of RSD1235

Abstract: These data suggest that RSD1235's clinical selectivity and AF conversion efficacy result from block of potassium channels combined with frequency- and voltage-dependent block of INa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
169
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 42 publications
(73 reference statements)
7
169
0
3
Order By: Relevance
“…Blockade of the ultrarapid delayed rectifier current I Kur (or Kv1.5) channel has been proposed as a novel target for the development of safer and potentially more effective atrial antiarrhythmic agents. 39 Four structurally distinct synthesized antiarrhythmic agents have been described as possessing I Kur block as part of their spectrum of actions: NIP-141, 40 AVE0118, 41,42 RSD1235, 43 and DPO-1. 44 The present study demonstrates that acacetin, a natural flavone I Kur blocker, also blocks I to and I KACh .…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of the ultrarapid delayed rectifier current I Kur (or Kv1.5) channel has been proposed as a novel target for the development of safer and potentially more effective atrial antiarrhythmic agents. 39 Four structurally distinct synthesized antiarrhythmic agents have been described as possessing I Kur block as part of their spectrum of actions: NIP-141, 40 AVE0118, 41,42 RSD1235, 43 and DPO-1. 44 The present study demonstrates that acacetin, a natural flavone I Kur blocker, also blocks I to and I KACh .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In animal models of AF and in a recent clinical study, vernakalant selectively prolonged the atrial refractory period without affecting ventricular refractoriness. [7][8][9] Vernakalant effectively converted acute-onset AF (AF lasting 3 to 72 hours) in a placebo-controlled phase 2 trial (nϭ56). 10 …”
Section: Clinical Perspective P 1525mentioning
confidence: 99%
“…Most drugs currently in use for treatment of atrial fibrillation are indiscriminate, targeting channels in both atrial and ventricular tissue and are therefore associated with life-threatening (ventricular) arrhythmias. Vernakalant (RSD1235) is a mixed voltage-and frequencydependent Na ϩ and atria-preferred K ϩ channel blocker (Roy et al, 2004;Fedida et al, 2005) under development for the acute conversion of atrial fibrillation to sinus rhythm. In recent phase II and III clinical trials, vernakalant has shown promise as an intravenous antiarrhythmic agent for rapid conversion of atrial fibrillation to sinus rhythm with an overall rate close to 52% within 90 min of infusion, compared with a placebo conversion rate of just 3.8% (Roy et al, 2005;Pratt et al, 2006;Stiell et al, 2006;Fedida, 2007).…”
mentioning
confidence: 99%